Characterization of trbC, a new F plasmid tra operon gene that is essential to conjugative transfer. - Maneewannakul, S (1991)
We have characterized a previously unidentified gene, trbC, which is contained in the transfer region of the Escherichia coli K-12 fertility factor, F. Our data show that the trbC gene is located between the F plasmid genes traU and traN. The product of trbC was identified as a polypeptide with an apparent molecular weight (Ma) of 23,500 that is processed to an Ma-21,500 mature protein. When ethanol was present, the Ma-23,500 polypeptide accumulated; the removal of ethanol resulted in the appearance of the processed mature protein. Subcellular fractionation experiments demonstrated that the processed, Ma-21,500 mature protein was located in the periplasm. DNA sequence analysis showed that trbC encodes a 212-amino-acid Mr-23,432 polypeptide that could be processed to a 191-amino-acid Mr-21,225 mature protein through the removal of a typical amino-terminal signal sequence. We also constructed two different Kmr gene insertion mutations in trbC and crossed these onto the transmissible F plasmid derivative pOX38. We found that cells carrying pOX38 trbC mutant plasmids were transfer deficient and resistant to infection by F-pilus-specific phages. Transfer proficiency and bacteriophage sensitivity were restored by complementation when a trbC+ plasmid clone was introduced into these cells. These results showed that trbC function is essential to the F plasmid conjugative transfer system and suggested that the TrbC protein participates in F-pilus assembly.